Spatial Distribution of Root and Crop Yield in a Bamboo Based Agroforestry System - Bhol, N.; Nayak, H. (Indian Forester, 2014)
The studies on spatial distribution of roots and yield of intercrops in a Dendrocalamus strictus (Salia bamboo) based nd agroforestry system were carried out with planting bamboo clumps in two spacings (12m x 10m and 10m x 10m). In 2 year kharif, four intercrops including cowpea, blackgram, greengram and sesamum were grown along with bamboo and in the following rabi season, greengram, sunflower, toria and blackgram were grown. The growth of bamboo clumps and root intensity were significantly higher with all four intercrops over the clumps grown without intercrop. 2 The root intensity decreased with increase of distance from clump. At 1m distance it was 330/m while at 4m distance it 2 2 2 was 20/m . The highest root intensity was found at 0-15cm depth (317/m ) and lowest in 30-45 cm depth (29/m ).